Caries prevalence of school-going boys and girls according to cleaning methods and soft drink-taking frequency in different localities, in and around Guwahati City - Chandana Kalita; Bapukan Choudhary; Anjan Kumar Saikia; Pratap Chandra Sarma (Wolters Kluwer Medknow Publications, 2016)
Background: Dental caries is a multifactorial disease, causes of which are mostly understood nowadays. This disease is not only treatable but also preventable, if detected in its initial stage. In a developing country like India, facility of dental treatment is available mostly for urban population, whereas a very common approach of dental disease treatment is still traditional for the rural people. Objective: The objective of this study was to find out the prevalence of dental caries, teeth cleaning methods, and sweet and soft drink-taking frequency among boys and girls of Guwahati City and its nearby semi-urban and rural areas. Materials and Methods: Cross sectional study was carried out among school going boys and girls of 3-17 years group, using the modified WHO oral health survey form. The number of population was 2396 from urban locality, 2370 from semi-urban, and 2467 from rural. Results: Caries prevalence is much higher in urban (62.77%), contrary to rural where 76% of the sample is caries free. Those who take sweet occasionally suffered less or almost caries free (7.93% in urban and 0% in rural) than among those who consume it more than five times a day (90.75% in urban, 100% in semi-urban, and 99.33% in rural). Discussion and Conclusion: Urban localities are two times and semi-urban areas are 1.64 times more at risk of dental caries than rural areas. The odds ratio for cleaning frequency shows that the effect of cleaning by brush on caries is less (78%, not significant) than chewing stick while the risk associated with finger and charcoal use is about 19.63 times and 7.11 times, respectively.